Automatic generation of Data Warehouse Instances from Requirements - Pizarro, Carlos (2021)
Data Warehouse projects in organizations as a basis for obtaining in-formation are having a great development today. The maturity of generation methodologies has reached significant acceptance. This allows us to focus on addressing the study of the lack of adaptability to the high dynamics of the changes in requirements of this type of projects. Data Science and Natural Language Processing allow us to integrate areas of knowledge and provide tools to solve this problem. A methodological model is proposed to partially automate the stages of generation of Data Warehouse instances based on requirements.